Early detection of acute myocardial infarction: additional diagnostic information from serum concentrations of myoglobin in patients without ST elevation. Issue 6 (June 1990) - Ohman, E M; Casey, C; Bengtson, J R; Pryor, D; Tormey, W; Horgan, J H
Abstract : The value of the 12 lead electrocardiogram, serum total creatine kinase, creatine kinase MB isoenzyme, and myoglobin for the early detection of infarction was evaluated within one hour of admission to the coronary care unit in 82 consecutive patients with suspected myocardial infarction. The 51 patients in whom infarction was diagnosed during the first 24 hours after admission had a higher prevalence of ST elevation (64% v 11%), higher median serum myoglobin (136 micrograms/l v 34 micrograms/l), higher serum creatine kinase (77 IU/l v 34 IU/l), and higher MB isoenzyme (7 IU/l v 4 IU/l) than those in whom it was not. Stepwise logistic regression analysis in 70 patients in whom the electrocardiogram and serum myoglobin were suitable for analysis showed that serum myoglobin was the variable most closely associated with infarction, and contributed additional diagnostic information when ST elevation was entered into the model first. Serum myoglobin remained associated with myocardial infarction when patients who had had symptoms for less than six hours were analysed. An algorithm based on a rapid agglutination test for myoglobin and ST elevation on the electrocardiogram gave an accurate diagnosis in 82% of patients. This approach gave early and rapid recognition of acute myocardial infarction and warrants further examination.